Synthesis and characterizations of magnetic nanoparticles - Tan, Ching Hong (Universiti Malaysia Sarawak (UNIMAS), 2011)
Magnetic nanoparticles can be applied in various applications such as drug targeting and delivery, magnetic resonance imaging, electrochemical cells, capacitors and etc. However, these applications require narrow size distribution and uniform shape magnetic nanoparticles and the synthesis of these magnetic nanoparticles often result in a broad size distribution. In present study, thermal decomposition method was adapted to obtain a monodispersed size and uniform shape of Fe3O4 nanoparticles while coprecipitation method was adapted to synthesize MnFe2O4 nanoparticles and the cyclic voltammetry was applied to examine the electrochemical properties of MnFe2O4. The morphology, chemical composition and electrochemical properties of synthesized magnetic nanoparticles were characterized using SEM, TEM, AAS and CV respectively. It was found that by increasing concentration of Fe(acac)3, the Fe3O4 nanoparticles size increases, the addition of oleic acid created a more uniform nanoparticles and longer time duration of thermal decomposition had increased the size of Fe3O4 nanoparticles. MnFe2O4 nanoparticles size was affected by the heating temperature, the presence of surfactant PVP and the metal salt concentration with hydroxide ions. The highest specific capacitance of MnFe2O4 nanoparticles was found to be at 500 ˚C and the higher the mass of the MnFe2O4 nanoparticles, the higher the charge capacity.